Spontaneous initiation of parturition after two-days-course of lung maturation and controversies in management of pre-eclampsia: A case report - Eva Febia; . Rajuddin (Syiah Kuala University, 2011)
There have been many controversies on how we should treat patients with preeclampsia, how and when we should deliver the baby. This case report is purposed to evaluate one case of spontaneous parturition which ended up with vaginal delivery in one patient with preterm severe preeclampsia. We evaluate the best management which result in the best outcome for the patient and her baby. This is the case of Mrs N, 34 years old in 33-34 weeks gestational age with severe preeclampsia. When she came the blood pressure was 190/120 mmHg, protein urine +3. The blood pressure was controlled with nifedipine. The patient was given magnesium sulphate, N-acetyl cystein, and vitamin C as antioxidants. We were succeeded in completing two days of lung maturation with dexamethasone in order to give the best outcome for the baby. However, at the end, after two days of lung maturation, the patient started to enter the active phase of parturition spontaneously without labor of induction. We hypothesized that the high level of corticosteroid stimulated by the fetus initiated the process of labor. Patient delivered baby boy, 1300 grams, Apgar Score 7/8 that breathed spontaneously in room air. The patient’s condition was improving after parturition. Nifedipine, magnesium sulphate was considered the best management in pre-eclampsia. Short course of lung maturation with dexamethasone was also considered to be beneficial for the baby. However, the initiation of parturition and the use of antioxidant as well as n-acetyl cystein in this patients was under debatable discussion.